Solution of Earth orientation parameters in the frame of new Earth orientation Catalogue - Vondrak, J.; Ron, C. (Кинематика и физика небесных тел, 2005)
The new Earth Orientation Catalogue was recently derived, based mostly on the ARIHIP and Tycho-2 Catalogues that were combined with ground-based optical observations of latitude and Universal Time variations in the 20th century. The solution of Earth orientation parameters, based on this new star catalogue and the new IAU model of precession-nutation, is presented.